Treatment of cervical intraepithelial lesions (2017)
Precancerous cervical lesions precede the development of invasive cervical cancer by 10–20 years, making cervical cancer preventable if these lesions are detected and effectively treated. Treatment has evolved in the last few decades and now includes ablative options that can be performed in lower‐resource settings where surgical excision is not feasible or routinely available. Gas‐based cryotherapy, which freezes cervical tissue to induce localized necrosis, is the most commonly used ablative treatment. However, its implementation in low‐resource settings is difficult because the refrigerant gas can be difficult to procure and transport, and is expensive. New cryotherapy devices that do not require an external supply of gas appear promising. Thermal coagulation, which burns cervical tissue to induce necrosis, has become more widely available in the last few years owing to its portability and the feasibility of using battery‐powered devices. These two ablative treatments successfully eradicate 75%–85% of high‐grade cervical lesions and have minor adverse effects.